1995
DOI: 10.1177/026921559500900204
|View full text |Cite
|
Sign up to set email alerts
|

The emotional consequences of falls for older people and their families

Abstract: The emotional impact on elderly patients and their relatives of falls has not been widely studied. The authors of this study interviewed a consecutive series of 69 elderly patients admitted to hospital after a fall, together with their carers, to assess the significance of any fear of future falls and to examine other variables that might be associated with such fears. Whilst 25% of the patients expressed a significant fear of falling, 58% of the carers interviewed reported a great fear that their relative/fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 9 publications
5
52
0
1
Order By: Relevance
“…We expect the impact of our non-response on the correlates of fear of falling and avoidance of activity to be limited not only as our associations showed to be similar to those in other studies but also as the impact of non-response on studied associations showed to be quite small [24]. Second, prevalence rates of fear of falling and avoidance of activity may also have been under-reported since reluctance to acknowledge fear of falling among older people has been observed [12,25]. Third, we assessed both fear of falling and avoidance of activity with a one-item question, which may not be the most optimal way to measure a construct.…”
Section: Discussionsupporting
confidence: 60%
“…We expect the impact of our non-response on the correlates of fear of falling and avoidance of activity to be limited not only as our associations showed to be similar to those in other studies but also as the impact of non-response on studied associations showed to be quite small [24]. Second, prevalence rates of fear of falling and avoidance of activity may also have been under-reported since reluctance to acknowledge fear of falling among older people has been observed [12,25]. Third, we assessed both fear of falling and avoidance of activity with a one-item question, which may not be the most optimal way to measure a construct.…”
Section: Discussionsupporting
confidence: 60%
“…FoF is associated with poorer health, reduced mobility and social activity, greater frailty, balance and gait prob-lems, modified postural control, psychological distress in the form of anxiety and depression, poorer quality of life (QoL), and increased likelihood of nursing home admission [1][2][3][4][5][6][7][8][9][10]. FoF has been linked to subsequent falls [10][11][12] and vice versa, resulting in a spiraling incidence of both phenomena and subsequent functional decline [1,9,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…www.kan.or.kr 입원환자의 낙상은 손상의 주요원인이며 심각한 신체적 손상 뿐 아니라 (Hendrich, Nyhuis, Kippenbrock, & Soja, 1995;Liddle & Gilleard, 1984) 낙상 후 손상으로 재원일수가 길어지고 검사나 수술로 인해 추가적인 비용부담이 발생하며, 의료과실로 소송이 제기되는 가장 흔한 원인이 되고 있다 (Bergland & Wyller, 2004). (Morse, Prowse, Morrow, & Federspeil, 1985), Hendrich Fall Risk Model (Hendrich et al, 1995), St. Thomas's Risk Assessment Tool in Falling Elderly Inpatients (Oliver, Britton, Seed, Martin, & Hopper, 1997 (Graf, 2008;Perell et al, 2001;Razmus et al, 2006).…”
unclassified